Collaborative cognition : children negotiating ways of knowing - Bearison, David J. (Advances in discourse processes., 2002)
Using the interpersonal event as the unit of analysis, this work examines how children interactively co-construct knowledge and ways of knowing social contexts, through a range of contributing motivational and emotional factors.